Faktor Yang Mempengaruhi Pengambilan Keputusan Wisatawan Untuk Berkunjung Ke Wisata Halal - Somadi; Cupian, Cupian; Hayati, Amelia (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This research aims to study the factors that influence halal tourist visits. Design/Methode/Approach: This research uses a quantitative approach with data analysis techniques, namely structural equation modeling. Research Finding: Travel motivation, accommodation, ease of obtaining halal food and drinks, tourist attractions, destination image, sharia tourist guides, promotions, facilities, religiosity, accessibility, and safety have a significant influence on tourists' decision-making, while knowledge and electronic word of mouth do not have a significant influence on decision making. tourists' decision to visit halal tourism. Theoretical contribution/Originality: The study provides valuable insights into the dynamics of this emerging sector. It highlights the significance of factors such as religiosity, accessibility, and security in influencing tourist decisions within the halal tourism domain, thus adding to the body of knowledge concerning the behavior of Muslim travelers and the development of halal-friendly destinations. Practitioner/Policy implication: The study provides actionable insights for improving destination competitiveness, enhancing visitor experiences, and strategic marketing of halal tourism products and services. Research limitation: The research focuses on halal tourism in Kampung Daun and Eco Sunnah.